Advancing Therapeutic Strategies in Atopic Dermatitis: Emerging Targets and Personalized Approaches - Yang Lo; Ting-Ting Cheng; Chi-Jung Huang; Yu-Che Cheng; I-Tsu Chyuan (Biomolecules)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder marked by intricate interplay among skin barrier dysfunction, immune dysregulation, and microbial dysbiosis. While therapeutic advancements targeting T helper 2 (Th2) cytokines, such as interleukin (IL)-4 and IL-13, and the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway have yielded promising outcomes, a significant proportion of patients still experience inadequate relief, particularly from persistent pruritus. Achieving minimal disease activity remains an unmet clinical priority and a cornerstone of effective AD management. This review provides an in-depth analysis of current therapeutic approaches and integrates findings from recent biologic studies, with a particular focus on innovative strategies under active investigation. These approaches include targeting components of the innate immune system, such as thymic stromal lymphopoietin (TSLP) and IL-1 family cytokines; the adaptive immune system, including OX40-OX40L interactions and Th17- and Th22-related cytokines; and mechanisms associated with pruritus, such as IL-31, histamine receptors, and neurokinin 1 receptor. Emerging insights underscore the transformative potential of personalized therapeutic regimens tailored to the distinct endotypes and severity of AD. Advances in deciphering the pathogenesis of AD are unlocking unprecedented opportunities for precision medicine, offering renewed hope for improved outcomes in this multifaceted and heterogeneous condition.